Filipino Nurses’ Experiences in Conducting Health Education in the Emergency Room - Rubio, Rica Rose May; Sali, Al-Sharif (Alta Dharma Publisher, 2022)
Background: Nurses face more challenges in delivering health education in contexts where the milieus are not well defined, such as the emergency room (ER). Objective: This study aimed to explore the experiences of ER nurses in conducting health education inside the ER and identify the most common barriers therein. Method: A phenomenology approach was utilized involving Ten ER nurses purposely chosen for the interview. Braun and Clarke's framework was used in data analysis. Results: The participants' experiences were expressed and represented in the following themes and subthemes: The theme: Experiences in Conducting Health Education in the ER consists of three subthemes: (1) Routine Work in the ER, (2) Length, Frequency, and Manner in Conducting Health Education, and (3) Feelings Derived from Conducting Health Education. The theme: Barriers to Health Education in the Emergency Room comprised the six subthemes: (1) Lack of Time, (2) Language Barrier, (3) Patient’s Psychosocial State, (4) Patient’s Cultural Beliefs, (5) Nurse’s Lack of Knowledge, and (6) Lack of Infographic Materials. Recommendation: Based on the findings, the conduct of health education in the ER can be done. Knowing the barriers can assist ER nurses and the hospital administration in producing the best solutions to solve them, thereby improving the quality of nursing care in the emergency room